FAMILY IN DISPLACEMENT AND ITS ROLE IN CULTURAL ADAPTATION AND NATIVE LANGUAGE PRESERVATION - Trifunovic, Maja (Serbian political thought, 2024)
This paper analyzes the challenges and opportunities faced by families in a diaspora regarding cultural adaptation and native language preservation. In the modern world, where migration becomes more frequent, families that move into new cultural environments often face a dilemma between integrating into the host country and preserving their own cultural identity through nurturing the native language and tradition of the countries from which they originate. In the context of globalization, the family proves to be a critical unit that not only transmits language and cultural values but also forms the identity of each of its members, providing him/her with the possibility to develop multiculturally in all personality aspects. Through the review of relevant literature and published studies, this paper examines factors that affect the success of the adaptation of new generations, including the role of social support, educational institutions, and intergenerational relations. The paper also explores the strategies families use to preserve their native language, which is critical in maintaining cultural identity. Daily communication in the native language, cultural events, manifestations, and participation in educational programs ensure that younger generations remain connected to their roots. Families often take an active role in creating communities that support language and culture preservation, thus contributing to the richness of multicultural societies. This paper contributes to the understanding of the dynamics of identity in the diaspora and emphasizes the educational role of family structures in the process of cultural adaptation and openness in accepting other cultures. The paper’s conclusions suggest that language and culture preservation is possible through a combination of individual efforts, community support, and adapted educational programs. The paper provides guidelines for future research and practice, emphasizing the need to develop effective diaspora family support models to preserve linguistic and cultural heritage.
Keywords: the expatriate family; cultural adaptation; native language